Apakah Frekuensi Rapat DPS, Profitabilitas dan Surat Berharga Syariah Berpengaruh pada Islamic Social Reporting Index? - Marefsi, Ethika Suri; Kurnia, Kurnia; Pratama, Febrial (AKTSAR: Jurnal Akuntansi Syariah, 2021)
This research aims to identify the factors that impact the Islamic Social Reporting of Sharia Banks in Indonesia. The dependent variable used is Islamic Social Reporting disclosure. At the same time, the independent variables are the meeting frequency of the sharia supervisory board, profitability, and the issuance of shariah securities. The population is all Islamic Banks listed on Financial Services Authority in Indonesia during the period 2014-2020. There are 11 companies selected as samples based on the purposive sampling method. This research uses the panel data regression tested by Eviews 11 software. The result found that the issuance of shariah securities had a positive impact. Although, the meeting frequency of shariah supervisory boards and profitability had no impact on Islamic Social Reporting. These results can be used as a reference for further research on the impact meeting frequency of shariah supervisory board, profitability, and the issuance of shariah securities. In addition, it can also be used as knowledge for companies that the issuance of Islamic securities can be a tool for Islamic banks to disclose Islamic Social Reporting fully. It is hoped that the government will make official standard rules regarding social responsibility reporting for Islamic entities. Keywords: Islamic Social Reporting; meeting frequency of shariah supervisory board; profitability; sharia securities issuance